The Role Of Engagement In Mediating The Effect Of Halal Storytelling On Brand Awareness In The Context Of Msme Marketing On Instagram And Tiktok - Sekar Yanti, Vanda; Mulia Wibawa, Berto (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
This study investigates the influence of halal storytelling on brand awareness, with engagement serving as a mediating variable in the context of Instagram and TikTok marketing for micro, small, and medium enterprises (MSMEs). As digital platforms become increasingly central to halal-conscious consumers, the use of ethical and religious narratives has emerged as a powerful branding strategy. Using a quantitative approach and data collected through an online survey, this research analyzes responses from 165 followers of MSME brands active on Instagram and TikTok. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that halal storytelling has a significant positive effect on engagement, which in turn positively influences brand awareness. Additionally, engagement significantly mediates the relationship between halal storytelling and brand awareness, suggesting that interaction and involvement on social media platforms amplify the effectiveness of halal narratives. These findings provide practical implications for MSME marketers seeking to enhance brand positioning through value-driven content strategies on social media.